PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MURDER UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI GAYA DI KELAS VIII SMP NEGERI 5 KUANTAN MUDIK - Nopitalia, Asni; ', Azizahwati; ', Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
APPLICATION OF MODEL COOPERATIVE LEARNING TYPE MURDER TO INCREASE STUDENT MOTIVATION ON MATERIAL FORCE IN CLASS VIII SMP NEGERI 5KUANTAN MUDIKAsni Nopitalia, Azizahwati, AzharEmail: asninopitalia94@gmail.com, HP: 085271174292Zasay_yon@yahoo.com, azhar_ur2010@yahoo.comPhysics Education Study ProgramFaculty of Teacher’s Training and EducationUniversity of RiauAbstract: The problems encountered are the lack of motivation possessed by the students causing low student learning outcomes. The low learning outcomes of science students of grade VIII SMP NEGERI 5 Kuantan Mudik is caused by students less active and feel not interested in learning, students feel bored in teaching and learning process, and lack of motivation obtained by students in learning. So that will have an impact on student learning outcomes. Type MURDER cooperative learning has a dominant perspective in contemporary education that focuses on how students acquire, store and process what they learn and how they occu. The subjects of this research are students of class VIII with the number of students 19 people. This research is a pre-experiment One Group Pretest-Posttest Design. The data collection used is a questionnaire of learning motivation ARCS, where students are given a questionnaire of early learning motivation (pretest) in advance to see the level of initial motivation of students, after that given treatment or treatment by applying the learning model MURDER. Then the researcher gave a questionnaire of final learning motivation (posttest). Next, the data were analyzed descriptively to see the improvement of learning motivation. This research aims to improve the learning motivation of Physics Science. Pretest student's motivation score of 3.49 and student's final learning motivation score (posttest) got result of 3,98. Experienced an increase of 0.49 points. So it can be concluded that the application of cooperative learning model type MURDER can improve students' learning motivation on the material force in class VIII SMP Negeri 5 Kuantan Mudik.Keywords: Model of Cooperative Learning Type MURDER, Student LearningMotivation Materi Force.